P-461 Pre-selected for an award: A 16-year bicentric retrospective analysis of ovarian tissue cryopreservation (OTC) in paediatric patients: indications, results and outcome. (6th August 2021) - Grellet-Grün, M; Delepine, B; Le Van Quyen, P; Durlach, A; Greze, C; Ladureau-Fritsch, L; Lichtblau, I; Canepa, A S; Becmeur, F; Liné, A; Paillard, C; Pluchart, C; et al.
Abstract: Study question: What is the outcome of ovarian tissue cryopreservation (OTC) in paediatric patients from the beginning of its setting in two different French centres? Summary answer: In our cohort of 75 paediatric patients who underwent OTC, the mean age, malignancy rate and survival rate were 9.7 years, 70.7% and 77.3% respectively. What is known already: Cancer treatments of last decades improve the survival rate of children and adolescents; however chemo- and radiotherapy result in gonadal damage leading to acute ovarian failure and sterility. The preservation of fertility is now an integral part of care of children requiring gonadotoxic treatments. Currently OTC represents the only possibility of preserving the potential fertility in prepubertal girls. OTC is an effective fertility preservation option which allows long-term storage of primordial follicles, subsequent transplantation restores endocrine function and fertility. The efficacy of these techniques is well-demonstrated within adult population but the data are poor for paediatric patients. Study design, size, duration: This is a retrospective study of OTC practice of two French centres from January 2004 to May 2020. Participants/materials, setting, methods: A total of 75 patients from paediatrics units underwent cryopreservation of ovarian tissue before gonadotoxic therapy for malignant or benign diseases. The ovarian cortex was cut into fragments and the number of follicles per square millimeter was evaluated histologically. The long-term follow-up includes survival rate, hormonal and fertility status. Main results and the role of chance: The mean age at OTC of 75 patients was 9.7 years [0.2 – 20], 32% were postpubertal. 53 had malignant disease and 22 had non-malignant disease. The most frequent diagnoses in this cohort included acute leukemia, hemoglobinopathies and neuroblastoma. Indication for OTC was stem cell transplantation for 78.7% (n = 59) girls. A third of each ovary was collected for 62, 7% (n = 47) patients, a whole ovary for 33, 3% (n = 25) patients and a third of one ovary alone for 4, 0% (n = 3) patients. An average of 17 fragments [5-35] per patient was cryoconserved. A correlation was found between age and the number of fragments (p < 0.001). More fragments were obtained from partial bilateral harvesting than from whole ovary harvesting (p < 0.05). Histological analysis of ovarian tissue showed a median of 6.0 primordial follicles/mm2 [0.0–106.5] and no malignant cells were identified. A negative correlation was found between age and follicular density (p < 0.001). Median post-harvest follow-up was 92 months [1–188]: 17 girls had died, 12 were still treated for their pathology and 46 were in complete remission. Of all patients, 29 have been subject to hormonal status evaluation and 26 were diagnosed with premature ovarian insufficiency (p < 0.001). One patient had undergone thawed ovarian tissue transplantation. Limitations, reasons for caution: This study is a retrospective analysis. The cohort was not compared with a control group who did not undergo OTC or with an adult population. Furthermore, many of these girls are still young and do not intend to use the transplantation of thawed ovarian tissue yet. Wider implications of the findings: OTC should be proposed to all girls with high risk of developing premature ovarian insufficiency following gonadotoxic therapies in order to give them the possibility of fertility and endocrine restoration. Trial registration number: Not applicable